THE EFFECT OF DIVIDEND POLICY AND PROFITABILITY ON COMPANY VALUE WITH LIQUIDITY AS AN INTERVENING VARIABLE IN MANUFACTURING COMPANIES - Olandari Mulyadi; Putri Intan Permata Sari (Jurnal Ipteks Terapan, 2023)
The purpose of this research is to find out the dividend policy and profitability of the value of a company with liquidity as an intervening variable in a manufacturing company . The object of the research was manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The population in this study was 198 manufacturing companies in the 2017-2021 period. The sample collection method uses purposive sampling , with a total sample of 65 companies. The analytical method of this study is to use path analysis using the SPSS 25 test tool . The results of this study indicate that dividend policy partially has no effect on liquidity with a significant value of 0.858. Profitability partially affects liquidity with a significant value of 0.003. Dividend policy partially has no effect on firm value with a significant value of 0.317. Profitability partially affects firm value with a significant value of 0.001. Liquidity partially affects firm value with a significant value of 0.044. There is no indirect effect, between dividend policy on firm value through liquidity as an intervening variable There is no indirect effect, between profitability on firm value through liquidity as an intervening variable.